2022
DOI: 10.1038/s41467-022-34742-3
|View full text |Cite
|
Sign up to set email alerts
|

An atlas of amyloid aggregation: the impact of substitutions, insertions, deletions and truncations on amyloid beta fibril nucleation

Abstract: Multiplexed assays of variant effects (MAVEs) guide clinical variant interpretation and reveal disease mechanisms. To date, MAVEs have focussed on a single mutation type—amino acid (AA) substitutions—despite the diversity of coding variants that cause disease. Here we use Deep Indel Mutagenesis (DIM) to generate a comprehensive atlas of diverse variant effects for a disease protein, the amyloid beta (Aβ) peptide that aggregates in Alzheimer’s disease (AD) and is mutated in familial AD (fAD). The atlas identifi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 56 publications
2
31
0
Order By: Relevance
“…Substitutions are extremely context-dependent, with the impact of each depending on the physicochemical context in the structure. Consistent with other indel mutagenesis studies, we observed that deletions were in general more deleterious than insertions [1,6,30,31]. This effect becomes stronger with increasing length for both insertions and deletions as well (Additional file 3: Fig S8).…”
Section: Kir21 Surface Expressionsupporting
confidence: 90%
See 4 more Smart Citations
“…Substitutions are extremely context-dependent, with the impact of each depending on the physicochemical context in the structure. Consistent with other indel mutagenesis studies, we observed that deletions were in general more deleterious than insertions [1,6,30,31]. This effect becomes stronger with increasing length for both insertions and deletions as well (Additional file 3: Fig S8).…”
Section: Kir21 Surface Expressionsupporting
confidence: 90%
“…A prior indelscanning work provided evidence for this belief, as it revealed that most long indels are deleterious. Departures from this trend were also highly specific to the particular amyloid system, with idiosyncratic effects of large deletions being driven by exposure of a nucleating core and not generalizable to well folded proteins [1]. Based on this, we chose as default lengths 1, 2, and 3 amino acid-long indels, allowing us to capture the most relevant natural variation and observe any interesting length-dependent fitness effects while still maximizing sequencing capacity.…”
Section: A Methods To Generate Libraries Containing Point Insertion A...mentioning
confidence: 99%
See 3 more Smart Citations